Spoiling Tibet China and resource nationalism on the roof of the world - Lafitte, Gabriel (London Zed Books, 2013)
The mineral-rich mountains of Tibet, hitherto largely untouched by China's growing economy, are now to be the site of massive investment in copper, gold, silver, chromium and lithium mining for the world's factory, with devastating environmental and social outcomes. Spoiling Tibet is the first book that investigates mining at the roof of the world - an entirely unique authoritative guide through the torrent of online posts, official propaganda and exile speculation.
Tibet in its own right -- Gold rush in Tibet -- Reach of the revolutionary state -- Chromite globalization -- Capitalizing on Tibet : privatizing the treasure house -- Intensive exploitation -- Conclusion.
"Further reading on Tibet": pages [196]-197.
Includes bibliographical references and index.
Keywords: Mineral industries -- Social aspects -- China -- Tibet Autonomous Region; Mineral industries -- China -- Tibet Autonomous Region; Acid pollution of rivers, lakes, etc. -- China -- Tibet Autonomous Region; Water -- Pollution -- China -- Tibet Autonomous Region; Pollution; Natural areas -- China -- Tibet Autonomous Region; Tourism -- China -- Tibet Autonomous Region